The end of the welfare state? : responses to state retrenchment - Svallfors, Stefan; Taylor-Gooby, Peter (Routledge/European Sociological Association studies in European societies, 1999)
Using the findings from up-to-date attitude surveys in Europe East and West, the US and Australasia, this book shows that, contrary to the claims of experts and policy-makers, the welfare state is still highly popular amongst citizens.